Synthesis Of Bio-Aviation Fuel From Candlenut (Aleurites Moluccanus) Oil Using Supercritical Carbon Dioxide Extraction - Abdaslam Shaah, Marwan Abdulhakim (2022)
There is increasing interest in producing bio-aviation fuel from non-edible crops to reduce the amount of fossil fuels consumed annually. Moreover, bio-aviation fuel produced from renewable resources can significantly reduce environmental pollution by lowering greenhouse gas (GHG) emissions. The present study aimed to synthesize bio-aviation fuel from candlenut oil as an alternative fuel. The extraction of oil from candlenut seeds was conducted using supercritical CO2 (scCO2). The oil yield increased as the scCO2 pressure, temperature, and extraction time increase. The central composite design (CCD) of experiments was used to design the experimental conditions for candlenut oil extraction. Using response surface methodology (RSM), the experimental conditions were optimised for maximum oil extraction. At a scCO2 extraction temperature of 60 oC, pressure of 30 MPa, and 90 min reaction time, maximum of 65±0.3% of candlenut oil was extracted. The modified Gompertz mathematical model was utilized to elucidate lipids extraction behavior from candlenut seeds using scCO2.